Evaluating the Application of E-Government Services From the Beneficiaries Perspectives in Saudi Arabia - Alhamoudi, Salwa; AL-Ayed, Sura (The Arab Journal of Administration, 2019)
The aim of this study was to evaluate the application of the e-government services in their various dimensions (appearance, interaction, financial exchange, integration) from the point of view of the beneficiaries in the Riyadh region of Saudi Arabia. Accordingly, a field study was conducted to identify the degree of application of e-government services and discuss the most important factors associated with e-government framework. A survey research method based on quantitative technique was used, with a sample size of (386) beneficiaries of e-government services. Several results were reached, the most important of which was that the evaluation of the application of e-government was high. In analyzing the dimensions of the application of e-government services (appearance, interaction, financial exchange, integration), the financial exchange came on the top level of ranking the factors. Followed by the appearance then integration of the service. Finally, the interaction came at the last level. The results also showed that there were statistically significant differences at the level of (α0.05) in the degree of evaluation of the application of e-government services due to the gender variable of the respondents and on all dimensions. The study discussed the results and presented a set of recommendations to improve the application of e-government services, the most important is the need to develop the necessary plans for the rehabilitation and training of service providers in line with the requirements of change and is compatible with the applications of e-government projects.